GAMBARAN KUALITAS TIDUR DAN HEMOGLOBIN PADA REMAJA PUTRI - Walukow, Deon; Berhimponb, Siemona Lydia Eunike; Rambert, Glady Inri (Universitas Sam Ratulangi, 2025)
Background: Sleep is an essential biological need, especially during adolescence, a period of significant physical and hormonal changes. Poor sleep quality can affect health, including lowering hemoglobin levels, which increases the risk of anemia. In Indonesia, the prevalence of anemia among female adolescents aged 15–24 years is 32%, but data on sleep quality and hemoglobin levels in Minahasa Regency are limited. Objective: To describe the sleep quality and hemoglobin levels of female adolescents at SMA Kristen Sonder Minahasa Regency. Methods: This cross-sectional study involved 30 female adolescents selected through purposive sampling. Sleep quality data were collected using the Pittsburgh Sleep Quality Index (PSQI), and hemoglobin levels were measured using a hematology analyzer.Results: The study results showed that respondents with poor sleep quality totaled 24 individuals (80.00%), while those with good sleep quality numbered 6 individuals (20.00%). For hemoglobin levels, 27 respondents (90.00%) were in the normal category, and 3 respondents (10.00%) had low hemoglobin levels. Conclusion: Most female adolescents at SMA Kristen Sonder had poor sleep quality, and the hemoglobin levels of the participant were in the normal range. Keywords: Sleep quality; Hemoglobin; Female Adolescents